Pengaruh Health Education Pemeriksaan Payudara Sendiri (SADARI) terhadap Pengetahuan dan Praktik Deteksi Dini Kanker Payudara di PP Darul Amanah Sukorejo Kendal - Risjcha bunga winata; Rahayu Winarti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Breast cancer is one of the diseases with the highest incidence rates among women and can cause death if not detected early. Breast self-examination (SADARI) is a simple method for detecting breast abnormalities early on. However, the knowledge and practice of breast self-examination (SADARI) among adolescent girls are still low. The purpose of this research is to determine the effect of health education on breast self-examination (BSE) on the knowledge and practice of early breast cancer detection at Pondok Pesantren Darul Amanah Sukorejo Kendal. Quantitative research method with a quasi-experimental design and a one group pretest-posttest design. A sample of 50 respondents with total sampling. Ethics test no: 03/EC-LPPM/UWHS/I-2026. Data analysis used the Wilcoxon test. The results showed that there is an influence of health education on knowledge with a p-value of 0.001 and on the practice of early breast cancer detection with a p-value of 0.001. It can be concluded that health education can enhance the awareness, understanding, and ability of adolescents to perform breast self-examination (SADARI) independently as an early detection effort for breast cancer, making it important to continue this practice sustainably.